Hepatoprotective potential and chemical characterization of Artocarpus lakoocha fruit extract (Bangladesh Journal of Pharmacology, 2018)
Artocarpus lakoocha fruits are widely consumed as food. The study was aimed at evaluating its hepatoprotective activity and chemical constituents. The extract was analysed by HPLC for the presence of flavonoids and phenolic compounds. Hepatoprotective potential was determined in mice following 8 days of extract or silymarin (standard therapy) administration. Hepatotoxicity was induced by administration of paracetamol (500 mg/kg). The blood and liver of treated and untreated mice were collected 24 hours post-paracetamol intoxication. HPLC analysis confirmed the presence of chromatotropic acid, quercetin, gallic acid, vanillic acid, cinnamic acid, ferulic acid and kaempferol. Acute toxicity study showed no observed effect at more than 2,000 mg/kg. The fruit extract prevented the rise in liver function tests and paracetamol related histopathological alterations. The hepatoprotective activity of extract was dose-dependent. This study confirms the preventive effect of methanolic extract of monkey jack fruits against paracetamol-induced liver toxicity.Video Clip of Methodology:7 min 25 sec:   Click to watch